Proceedings of the 15th International Conference on World Wide Web 2006
DOI: 10.1145/1135777.1135902
|View full text |Cite
|
Sign up to set email alerts
|

Detecting online commercial intention (OCI)

Abstract: Understanding goals and preferences behind a user's online activities can greatly help information providers, such as search engine and E-Commerce web sites, to personalize contents and thus improve user satisfaction. Understanding a user's intention could also provide other business advantages to information providers. For example, information providers can decide whether to display commercial content based on user's intent to purchase. Previous work on Web search defines three major types of user search goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(86 citation statements)
references
References 15 publications
(18 reference statements)
0
85
0
1
Order By: Relevance
“…According to Dai et al [49], the classification of queries into navigational and informational is not the only one possible. In electronic commerce, further understanding of commercial intents is crucial.…”
Section: Using Taxonomiesmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Dai et al [49], the classification of queries into navigational and informational is not the only one possible. In electronic commerce, further understanding of commercial intents is crucial.…”
Section: Using Taxonomiesmentioning
confidence: 99%
“…Hence, one may suggest that deciding whether an intent exists behind a query is in fact a necessary step before trying to retrieve possibly relevant documents. Dai et al [49] report some examples of the relationships between commercial/non-commercial intent and navigational/informational/transactional intents; "u2 music downloads" is a query with transactional and commercial intent whereas "collide lyrics" is a query with transactional and non-commercial intent. In general, commercial intents are behind queries composed of nouns referred to commerce (e.g., "walmart," "dvd," "price").…”
Section: Using Taxonomiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dai et al [6] classified web pages into commercial and non-commercial classes in an attempt to detect the online commercial intent of a page. This work is close to ours as some of the categories overlap, however the authors only used keywords from text and html attributes as features whereas we are combining non-topical features with word-based features.…”
Section: Related Workmentioning
confidence: 99%
“…It has been reported that about 40 percent of search queries involve potential commercial transactions. See Eisenmann, supra note 37; See also Dai, et al (2006) "Detecting Online Commercial Intention," World Wide Web Conference, Edinburgh, Scotland. 40 Search engines typically capture data on searches and accumulate this over time.…”
mentioning
confidence: 99%